Safety of non‐ablative fractional laser for acne scars within 1 month after treatment with oral isotretinoin: A randomized split‐face controlled trial. Issue 10 (29th August 2017) - Saluja, Sandeep S.; Walker, Matthew L.; Summers, Erika M.; Tristani‐Firouzi, Payam; Smart, David R.
Abstract : Background and Objective: Based on reports of poor wound healing and scarring, it is currently recommended that patients wait 6 months after completion of oral isotretinoin therapy before the safe initiation of laser treatment. Our aim was to evaluate the safety of non‐ablative fractional laser (NAFL) treatment for acne scars within 1 month after isotretinoin therapy. Study Design/Methods: This was a randomized split‐face controlled trial involving 10 patients with acne scars who had completed isotretinoin treatment. All patients received three treatments each spaced 4 weeks apart with an erbium‐doped 1550 nm NAFL on one side of the face within 1 month after isotretinoin therapy. The untreated side acted as a control. Wound healing and adverse effects as well as acne scar improvement were evaluated by two blinded dermatologists. Results: All patients demonstrated normal wound healing post NAFL treatments, and neither hypertrophic scars nor keloids were observed. Acne scar improvement was satisfactory. Conclusion: NAFL treatment for acne scarring appears to be well tolerated within 1 month of completing isotretinoin treatment. Dermatologists should reevaluate the current recommendation to wait 6 months after isotretinoin treatment for acne scar revision with lasers. Other larger studies are necessary to further challenge this dogma. Lasers Surg. Med. 49:886–890, 2017. © 2017 Wiley Periodicals, Inc.